Digital Payments and Consumptive Behavior Among Millennials and Gen Z: The Mediating Role of a Cashless Lifestyle - Ameliya, Putri; Zahra, Syahratu Intan Az; A’maliyatusolihah, Mila (Talent: Journal of Economics and Business, 2025)
Driven by cultural shifts in lifestyle and social interaction shaped by the cashless society trend, this study examines the influence of digital payment use on the consumptive behavior of millennials and generation Z by considering the cashless lifestyle as an intermediate variable. The purpose of this study is to find out the extent to which digital payments affect consumptive tendencies in the digital era. This study uses a quantitative approach with a survey method and is analyzed through the Partial Least Square (PLS) technique. The results of the study show that digital payments do not have a direct effect on consumptive behavior, but have an indirect effect through the characteristics of the millennial generation. In addition, both millennials and generation Z have a significant influence on consumptive behavior. The discussion shows that consumption in the younger generation is driven more by lifestyle and social factors than the convenience of technology alone. The conclusion of this study emphasizes the importance of financial literacy and wise consumption education in the midst of financial technology developments. Follow-up research is recommended using a qualitative approach to explore deeper psychological factors and expand the population so that the results can be generalized more broadly.